Community Participation and Mosquito Breeding Sites in Cimahi City: Current Conditions and Challenges in Dengue Fever Control - Faridah, Lia; Angga, Anggisti Nurdinda Chaerany Putri; Fauziah, Nisa; Jaya, I Gede Nyoman Mindra (Universitas Islam Bandung, 2025)
In 2021, Cimahi City recorded the 5th highest dengue fever (DF) cases among 27 districts/cities in West Java. Efforts to control DF have been going on for several decades, with one strategy being to involve community participation in eliminating mosquito breeding sites. This research evaluated community participation in Cimahi city by identifying mosquito breeding locations inside and outside the home. Samples were taken from 15 sub-districts in Cimahi city. The research population involved houses in 15 sub-districts, with a total sample of 1,560 houses representing each sub-district. Larval sampling was carried out in various water reservoirs, both natural and artificial, around residential areas. The successfully taken larvae were then identified and counted in the laboratory. The research showed that the most dominant mosquito breeding place was in bucket-type containers, namely 130 units (3.2%). Entomological data produced a free larva index (FLI) of 79.23%, a house index (HI) of 20.7%, a container index (CI) of 8.07%, and a Breteau index (BI) of 20.5%. This finding indicated a lack of community involvement in preventing vector-borne diseases by eliminating breeding sites. Cimahi city still had the potential to spread vector-borne diseases.